2021
DOI: 10.14740/cr1333
|View full text |Cite
|
Sign up to set email alerts
|

A Significant Increase of Estimated Glomerular Filtration Rate After Switching From Fenofibrate to Pemafibrate in Type 2 Diabetic Patients

Abstract: Background Dyslipidemia is one of the major risk factors for cardiovascular disease (CVD), along with hypertension, diabetes, smoking and obesity. Approximately 70% of CVD risk remains even after treatment of elevated low-density lipoprotein-cholesterol (LDL-C) by statins. High triglyceride (TG) and low high-density lipoprotein-cholesterol (HDL-C) level are potential therapeutic targets to prevent CVD. Fibrates were associated with a greater reduction in TG, and a greater increase in HDL-C. Fibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…However, reduction of serum UA by pemafibrate was not reported. Fenofibrate has URAT1 inhibitory effect, but pemafibrate may not have such effect, which was supported by our recent study that showed a significant increase of serum UA after the switching from fenofibrate to pemafibrate [ 60 ]. In this study, pemafibrate may decrease serum UA by reducing over-expressed URAT1 and GLUT9 due to insulin resistance, and by improving systemic insulin resistance, which may be supported by a significant and positive correlation between changes in serum UA and changes in TG at 12 months after the start of pemafibrate.…”
Section: Discussionmentioning
confidence: 62%
“…However, reduction of serum UA by pemafibrate was not reported. Fenofibrate has URAT1 inhibitory effect, but pemafibrate may not have such effect, which was supported by our recent study that showed a significant increase of serum UA after the switching from fenofibrate to pemafibrate [ 60 ]. In this study, pemafibrate may decrease serum UA by reducing over-expressed URAT1 and GLUT9 due to insulin resistance, and by improving systemic insulin resistance, which may be supported by a significant and positive correlation between changes in serum UA and changes in TG at 12 months after the start of pemafibrate.…”
Section: Discussionmentioning
confidence: 62%
“…Topiroxostat was reported to inhibit ABCG2 [8], which may lead to increase in serum creatinine due to reduced excretion of IS. We previously reported a significant increase in estimated glomerular filtration rate (eGFR), in spite of an increase in serum UA, by the switching from fenofibrate which inhibits ABCG2 to pemafibrate in type 2 diabetic patients [8,9], supporting an importance of ABCG2 for renal function. Hyperuricemia was associated with a greater incidence of end-stage renal disease [10].…”
Section: To the Editormentioning
confidence: 97%
“…We previously reported that the switching from fenofibrate to the selective peroxisome proliferator-activated receptor (PPAR) α modulator, pemafibrate, increased serum uric acid (UA) levels and reduced estimated glomerular filtration rate (eGFR) in patients with dyslipidemia [ 1 ]. Fenofibrate has a property to decrease serum UA by inhibition of urate transporter 1 (URAT1) by its major metabolite [ 2 ].…”
Section: To the Editormentioning
confidence: 99%
“…Although fenofibrate was reported to decrease the eGFR [ 3 ], the mechanism of fenofibrate-induced renal impairment has been remained unclear. Further, our previous discussion on such issue was premature [ 1 ]. Recently, the role of UA transporters has been clarified [ 4 ] ( Fig.…”
Section: To the Editormentioning
confidence: 99%